Shensu IV maintains the integrity of the glomerular filtration barrier and exerts renal protective effects by regulating endogenous hydrogen sulfide levels - Zhou, Shuhui; Zheng, Liping; Zheng, Tingxuan; Zhan, Haiyan; Lin, Qiuyuan; Wei, Jiaoao; Huang, Yong (Frontiers in Pharmacology, 2024)
Background: Nephrotic syndrome has a significant impact on global health, often leading to cardiovascular disease and high mortality due to limited effective treatments. This study investigates the efficacy of Shensu IV in a puromycin aminonucleoside (PAN)-induced rat model of nephropathy.Methods: Rat models and in vitro podocyte PAN nephropathy models were established with PAN and treated with Shensu IV. Renal function was evaluated by measuring urine output and protein content, while hydrogen sulfide (H2S) and oxidative stress markers were quantified in serum and podocyte lysates. We conducted histological examination on kidney tissues and analyzed molecular markers (CD2AP, nephrin, and PI3K/AKT pathway) using RT-qPCR and western blot.Results: Shensu IV significantly improved urine output and proteinuria, and attenuated glomerular damage, fibrosis, and mitochondrial swelling in PAN-treated rats. Mechanistically, Shensu IV enhanced endogenous H2S production, reducing oxidative stress and activating the PI3K/AKT pathway in vivo and in vitro. This facilitated the upregulation of the target genes CD2AP and nephrin, which are critical for maintaining glomerular integrity and improving renal function in PAN nephropathy models.Shensu IV and NaHS confer renal protection primarily by modulating oxidative stress and restoring the integrity of the glomerular filtration barrier through mechanisms involving the enhancement of the PI3K/AKT pathway and modulation of H2S levels. These findings suggest a promising therapeutic potential for these metabolites in the treatment of nephrotic syndrome.